How to interpret an unenhanced CT Brain scan. Part 1: Basic principles of Computed Tomography and relevant neuroanatomy - Thomas Osborne; Christine Tang; Kivraj Sabarwal; Vineet Prakash (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2016)
The aim of this article is to: Cover the basics of Computed Tomography (CT) Brain imaging. Review relevant CT neuroanatomy. A CT image is produced by firing x-rays at a moving object which is then detected by an array of rotating detectors (Figure 1). The detected x-rays are then converted into a computerised signal which is used to produce a series of cross sectional images.